Changes in irisin levels in patients with hyperemesis gravidarum - Kavak, E. C.; Kavak, S. B.; Ilhan, R.; Kaplan, S.; Bagci, H.; Kaya, M. (I R O G Canada, Inc, 2017)
Purpose: The aim of this study was to compare levels of serum irisin in hyperemesis gravidarum (HG) patients to healthy Materials and Methods: Twenty pregnant women with hyperemesis gravidarum (Group 1) and 20 healthy pregnant women (Group all of similar ages, body mass index, and all at similar pregnancy development comprised the study cohort. Fasting serum samples obtained and measured for irisin levels. Comparisons between groups were done by Mann Whitney U (MWU) test and p < 0.05 considered as statistically significant. Results: All the patients in groups 1 and 2 were primigravid and age, gestational week, and mass index values were similar. No statistically significant difference were present among these parameters (p > 0.05, MWU test). plasma irisin concentrations in group 1 were significantly higher (irisin (average +/- S D): 116.9 +/- 32.3 ng/ml vs. 87.7 +/- 26.2 ng/ml) pared to the control group. Conclusion: This study suggests a possible role of irisin, which might be involved in the pathology of
Keywords: Hyperemesis gravidarum; Primigravida; Irisin